ANALISIS PENERAPAN LATIHAN STRETCHING BERBASIS ROTATIONAL BODY MOVEMENT PADA PERENANG GAYA BEBAS USIA 15–18 TAHUN - Nurhayati Simatupang; Iqbal Amanda Sinulingga; Ulul Azmi; Ikhsan Rizky Akmil; Enjel Rianta Ambarita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the application of stretching exercises based on rotational body movement in freestyle swimmers aged 15–18 years. The study employed a qualitative method with a descriptive approach through literature review (library research). Data were obtained from scientific journals, books, and previous studies related to stretching, flexibility, body rotation, and freestyle swimming performance. The results indicate that stretching exercises based on rotational body movement have a positive effect on improving body flexibility, joint range of motion, and swimming efficiency. Flexibility helps the body rotate optimally, increases stroke reach, maintains a streamlined position, and reduces water resistance while swimming. Additionally, regular stretching exercises can help reduce muscle tension and minimize the risk of injury in swimmers. Based on the analysis of various literature sources, it can be concluded that stretching exercises based on rotational body movement are suitable for implementation in training programs for adolescent swimmers to improve movement quality and freestyle swimming performance.